Comparative study of laparoscopy-assisted and open radical gastrectomy for stage T4a gastric cancer. (May 2017) - Zhang, Fan; Lan, Yuanzhi; Tang, Bo; Hao, Yingxue; Shi, Yan; Yu, Peiwu
Abstract: Background: The feasibility and safety of laparoscopic-assisted gastrectomy as a first-line treatment for advanced gastric cancer is controversial, especially for patients with serous membrane invasion. This study was designed to evaluate and compare the clinical effect of laparoscopy-assisted and open radical gastrectomy for stage T4a gastric cancer. Materials and methods: We performed a retrospective analysis of the clinical data of 230 patients with stage T4a gastric cancer in our hospital from October 2006 to October 2008. A total of 111 patients with stage T4a gastric cancer underwent laparoscopic radical gastrectomy (LARG group), and 119 patients with stage T4a gastric cancer underwent open radical gastrectomy (ORG group). Clinical parameters, including incision length, operation time, blood loss, time to first flatus, time to first defecation, length of hospital stay, postoperative complications, one-year, three-year, and five-year disease-free survival rates, and the overall survival rate were analyzed via t-tests and chi-squared tests. Results: The incision length, blood loss, time to first flatus, time to first defecation, and length of hospital stay in the LARG group were significantly less than in the ORG group (P < 0.05). The mean operation time in the LARG group was similar to that in the ORG group (P > 0.05). Postoperative complications were significantly less in the LARG group than in the ORG group (P < 0.05). The one-year, three-year, and five-year disease-free survival rates were 83.8%, 67.6%, and 37.8% in the LARG group, respectively, and 81.5%, 65.5%, and 35.3% in the ORG group, respectively (P > 0.05). The one-year, three-year, and five-year survival rates were 89.2%, 72.1%, and 47.7% in the LARG group, respectively, and 87.4%, 68.1%, and 40.3% in the ORG group, respectively (P > 0.05). Conclusion: LARG for stage T4a gastric cancer not only has the advantage of being minimally invasive, but the postoperative complication rate is low and the clinical effects are satisfactory. Highlights: Long-term clinical outcomes were comparable between ORG and LARG. LARG for stage T4a gastric cancer has a low postoperative complication rate. LARG for stage T4a gastric cancer has satisfactory clinical effects.